Simplifying
5y + -2 = 4y + 7
Reorder the terms:
-2 + 5y = 4y + 7
Reorder the terms:
-2 + 5y = 7 + 4y
Solving
-2 + 5y = 7 + 4y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '-4y' to each side of the equation.
-2 + 5y + -4y = 7 + 4y + -4y
Combine like terms: 5y + -4y = 1y
-2 + 1y = 7 + 4y + -4y
Combine like terms: 4y + -4y = 0
-2 + 1y = 7 + 0
-2 + 1y = 7
Add '2' to each side of the equation.
-2 + 2 + 1y = 7 + 2
Combine like terms: -2 + 2 = 0
0 + 1y = 7 + 2
1y = 7 + 2
Combine like terms: 7 + 2 = 9
1y = 9
Divide each side by '1'.
y = 9
Simplifying
y = 9